2011
DOI: 10.1080/15325008.2011.596506
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Partial Discharges in Gas-insulated Switchgear by Ultra-high-frequency Technique and Classification by Adopting Multi-class Support Vector Machines

Abstract: Ultra-high-frequency signals are generated due to particle movement, floating conductors, corona, and surface discharges in gas-insulated switchgear. The ultra-high-frequency signal generated due to particle movement is independent of operating pressure and applied voltage. The bandwidth of the ultra-high-frequency signal formed due to corona and surface discharges vary with applied voltage. In a ternary plot, each type of discharge has a unique location. If a variety of discharge occurs simultaneously, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 25 publications
(27 reference statements)
0
23
0
Order By: Relevance
“…In [6][7][8][9] it was presented that using wavelet or wavelet packet decomposition extraction of energy features and the classification results were satisfactory, while the methods mentioned in these papers focused on selecting energy features among the leaf nodes in WPD tree. In this paper, according to the analysis of WPD of EM signals, it is found that, if the level of decomposition is not deep enough, there would not be effective parameters for classification.…”
Section: Features Selection For Em Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [6][7][8][9] it was presented that using wavelet or wavelet packet decomposition extraction of energy features and the classification results were satisfactory, while the methods mentioned in these papers focused on selecting energy features among the leaf nodes in WPD tree. In this paper, according to the analysis of WPD of EM signals, it is found that, if the level of decomposition is not deep enough, there would not be effective parameters for classification.…”
Section: Features Selection For Em Signalsmentioning
confidence: 99%
“…It can be seen that, conducted by SVD, E of floating PD, oil clearance PD and void PD in pressboard is constructed with a primary singular vector, while E of needle PD is constructed with two primary singular vectors. After executing these steps above, seven energy features are finally extracted, which are (8, 31), (8,10), (8,8), (7,7), (7,13), (5,3), (3,0). The first digit in bracket denotes the level of WPD; the second digit denotes the position of tree node in the level indicated by the first digit.…”
Section: Features Selection For Em Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The signals are preprocessed with a wavelet decomposition and use the coefficients of the levels as one of the features to train a binary SVM. In [19] the rejection of noise is not taken into account when testing the effectiveness of the algorithms. In a previous work [20], the authors of this paper systematically addressed the classification of PD with SVM.…”
Section: Introductionmentioning
confidence: 99%
“…In Peiqing et al (2012), the representation is based on a time-frequency map already used in measurements with high-frequency transformers in conventional methods with PRPD. Finally, in Umamaheswari and Sarathi (2011), support vector machines are used to classify signals but a previous training of the SVM is needed.…”
Section: Introductionmentioning
confidence: 99%